2011
DOI: 10.1088/2041-8205/732/1/l4
|View full text |Cite
|
Sign up to set email alerts
|

SGR 0418+5729—HOW DOES A YOUNG NEUTRON STAR SPIN DOWN TO A 9 s PERIOD WITH A DIPOLE FIELD LESS THAN 10 13 G?

Abstract: The period derivative bound for SGR 0418+5729 (Rea et al. 2010) establishes the magnetic dipole moment to be distinctly lower than the magnetar range, placing the source beyond the regime of isolated pulsar activity in the P −Ṗ diagram and giving a characteristic age > 2 × 10 7 years, much older than the 10 5 year age range of SGRs and AXPs. So the spindown must be produced by

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 34 publications
2
49
0
Order By: Relevance
“…With a dipole field below 10 13 G, in fact, it would be impossible to slow down the star to the observed 9.1 s period in less than ∼24 Myr, a time much longer than the estimated age of other SGRs/AXPs, unless SGR 0418+5729 had an exceptionally long period at birth. A possible solution was suggested by Alpar et al (2011) who have shown that if SGR 0418+5729 was born with a period >70 ms and a low dipolar field (B ≈ 10 12 G), the torque exerted by a fallback disk can spin down the star to the present period in 10 5 yr, ifṖ has to be below the observed upper limit. 10 The survival of multipolar field components ≈100 times stronger than the dipole over such a time span may, however, be an issue in the light of the known evolution of the dipolar field in magnetars (see Section 2.1).…”
Section: Discussionmentioning
confidence: 99%
“…With a dipole field below 10 13 G, in fact, it would be impossible to slow down the star to the observed 9.1 s period in less than ∼24 Myr, a time much longer than the estimated age of other SGRs/AXPs, unless SGR 0418+5729 had an exceptionally long period at birth. A possible solution was suggested by Alpar et al (2011) who have shown that if SGR 0418+5729 was born with a period >70 ms and a low dipolar field (B ≈ 10 12 G), the torque exerted by a fallback disk can spin down the star to the present period in 10 5 yr, ifṖ has to be below the observed upper limit. 10 The survival of multipolar field components ≈100 times stronger than the dipole over such a time span may, however, be an issue in the light of the known evolution of the dipolar field in magnetars (see Section 2.1).…”
Section: Discussionmentioning
confidence: 99%
“…Soon after the discovery of pulsars it was found that their spin periods are increasing, implying a loss rate of rotational energy, E rot , sufficiently high to power not only the pulsed radio emission, but also the bright radio/optical/X-ray nebulae observed around the most energetic pulsars. The first striking example was provided by the pulsar PSR B0531+21, whoseĖ rot =4.6×10 38 erg s −1 matches the total energy output of the surrounding Crab nebula 3 . Most of the spin-down power is lost in a Poyntingdominated wind rather than in beamed photons from the pulsar.…”
Section: Rotationmentioning
confidence: 99%
“…(2009), Alpar et al (2011), andÇ alışkan et al (2013). Here, we briefly describe the basic long-term evolutionary phases of a neutron star evolving with a fallback disk.…”
Section: Long-term Evolution Of Swift J18223-1606mentioning
confidence: 99%